2002
DOI: 10.1002/chir.10108
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of chiral compounds from unresolved peaks in capillary electrophoresis using multivariate calibration with experimental design and artificial neural networks

Abstract: Quantitation of optical isomers can be achieved even from incompletely resolved peaks with a multivariate calibration applying a combination of experimental design and artificial neural networks (ANN). Using the proposed approach, method development can be more efficient and analysis time shortened while quantitation of optical isomers with acceptable precision (+/-1-3%) can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…These concentration profiles are used as initial values in a constrained ALS [14] optimization procedure. When a three-way data is analyzed, Eq.…”
Section: Description Of the Als Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These concentration profiles are used as initial values in a constrained ALS [14] optimization procedure. When a three-way data is analyzed, Eq.…”
Section: Description Of the Als Methodsmentioning
confidence: 99%
“…Dohnal et al [13] used experimental design and artificial neural networks (ED-ANN) for quantitative analysis of chiral compounds in unresolved peaks from CE runs. Artificial neural networks (ANNs) have also been used for quantification in unresolved CE peaks by Bocaz-Beneventi et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…0.05% of the minor enantiomer could be detected. [99] demonstrated that quantitative analysis of chiral compounds in CE is also possible in the case of unresolved peaks. Deconvolution of overlapped peaks as proposed for HPLC is difficult to apply in CE because electropherograms are not always reproducible.…”
Section: Enantioseparations Of Nonracemic Mixtures Determination Of mentioning
confidence: 99%
“…Latorre et al [2] have used partial least squares (PLS) regression for the determination of amino acids in overlapped CE peaks. Dohnal et al [3] used experimental design and artificial neural networks (EDANNs) for quantitative analysis of chiral compounds in unresolved peaks from CE runs [3]. ANNs have also been used for quantification in unresolved CE peaks by BocazBeneventi et al [4].…”
Section: Introductionmentioning
confidence: 98%